Pemaknaan Perceived Social Support pada Mantan Penyalahguna Narkoba di Indonesia: Studi Kualitatif - Mulya, Isabella Sasqia; Pohan, Lifina Dewi (Universitas Muhammadiyah Metro, 2023)
Drug abusers have various kinds of vulnerabilities ranging from physiological and psychological. However, one quality that can promote the mental health of drug abusers is perceived social support. This research was conducted through a qualitative approach to explore the perceived social support of former drug abusers in Indonesia. Participants in this study are individuals with substance abuse problems who have undergone rehabilitation and have returned to the environment. The main result obtained in this study is that there is a change in perceived social support during the substance abuse problems period and rehabilitation until they return to the environment. This research implies that perceived social support is a factor that can be intervened to prevent relapse from the recovering addict.